A graded regeneration method for PEEK recycled powder from SLS 3D printing
Patent Information
- Application Number
- CN202611175317.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]已公开的 PEEK 粉末回收工艺绝大多数针对航空航天、汽车制造等工业领域,仅通过简单筛分、球磨整形调整粒径,未针对医用植入的纯度管控、残留单体脱除、内毒素控制进行工艺设计,无法达到《外科植入物用聚醚醚酮(PEEK)树脂》(YY/T 0660)的质量要求,再生粉末不能用于三类植入医疗器械的生产
[0074]1.全流程医用级管控,生物安全性完全满足三类植入物要求
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical additive manufacturing materials technology, specifically relating to a graded regeneration method for SLS 3D printing PEEK recycled powder. Background Technology
[0002] Polyether ether ketone (PEEK) has excellent mechanical properties, biocompatibility, corrosion resistance and radiation permeability. Its elastic modulus is close to that of human cortical bone, which can effectively avoid stress shielding effect. It has now become a core medical polymer material in the fields of craniofacial repair, spinal fusion, orthopedic implantation.
[0003] Selective laser sintering (SLS) is the mainstream 3D printing process for personalized PEEK medical implants. It can rapidly produce high-precision, customized prostheses based on patients' medical imaging data and is increasingly widely used in clinical practice. The SLS process requires preheating the powder to a high temperature close to its melting point (usually 340~380℃). After printing, only a small amount of powder is sintered into shape in the cavity. 60%~70% of the unsintered powder will undergo long-term high-temperature thermal oxidation, resulting in aging phenomena such as molecular chain breakage, molecular weight reduction, melt flow rate shift, and mechanical property degradation. At the same time, sintered micro-agglomerates, metallic impurities, and oligomer residues are easily mixed into the powder, making it unsuitable for direct reuse in printing medical implants.
[0004] Medical implantable PEEK powder is extremely expensive (tens of thousands of yuan per kilogram). If waste powder cannot be effectively recycled, it will significantly increase the production cost of personalized implants and hinder clinical adoption. However, current PEEK powder recycling technologies have the following significant drawbacks, making it difficult to meet the stringent requirements of medical implantation scenarios:
[0005] 1. Existing technologies are mostly geared towards industrial applications and do not meet medical implantation standards.
[0006] Most of the publicly available PEEK powder recycling processes are designed for industrial fields such as aerospace and automobile manufacturing. They only involve simple sieving and ball milling to adjust the particle size, without process design for purity control, residual monomer removal, and endotoxin control for medical implants. Therefore, they cannot meet the quality requirements of "Polyetheretherketone (PEEK) Resin for Surgical Implants" (YY / T 0660), and the recycled powder cannot be used in the production of Class III implantable medical devices.
[0007] 2. Lack of aging and grading treatment resulted in poor batch stability.
[0008] A few technical solutions involving the recycling of medical PEEK powder do not differentiate between the degree of thermal aging of the powder. They mix powders with different degrees of degradation and process them uniformly, resulting in large batch-to-batch fluctuations in the molecular weight and mechanical properties of the recycled powder and low performance retention. It can usually only be reused 1 to 2 times, which is not economical and has insufficient production stability, and cannot meet the consistency requirements of mass production of medical implants.
[0009] 3. Lacking a molecular weight repair mechanism, the decline in mechanical properties is irreversible.
[0010] Current recycling processes primarily rely on physical sieving and morphology shaping, failing to effectively repair the molecular chain breakage caused by SLS high-temperature aging and thus unable to reverse the decline in powder mechanical properties. Implants printed with recycled powder exhibit significantly lower tensile strength, flexural strength, and impact resistance than those printed with virgin powder, posing long-term clinical safety risks of fracture and deformation.
[0011] 4. Lack of control over medical-grade impurities poses a high risk of biocompatibility problems.
[0012] Existing recycling processes lack systematic steps for removing residual monomers and oligomers, and have not established aseptic production and packaging procedures. Impurities such as residual bisphenol A monomers, oligomers, and processing aids in the recycled powder cannot be effectively removed, and endotoxin levels are prone to exceeding standards, making it difficult to pass the biocompatibility evaluation for Class III medical devices, and posing risks of clinical infection and rejection.
[0013] In summary, there is an urgent need to develop an SLS 3D printing PEEK powder regeneration method that is compatible with medical implant-grade standards, can effectively repair aging properties, has high batch stability, and can be reused multiple times, to fill the technological gap in closed-loop recycling of medical-grade PEEK powder. Summary of the Invention
[0014] The purpose of this invention is to address the shortcomings of existing technologies by providing a graded regeneration method for SLS 3D printing PEEK recycled powder, focusing on solving the following four core technical pain points in existing technologies:
[0015] Most existing publicly available PEEK powder recycling technologies are geared towards industrial applications such as aerospace and automotive manufacturing. They only involve simple sieving and ball milling to adjust particle size, and do not establish impurity control systems for Class III implantable medical devices. They lack dedicated processes for residual monomer removal, endotoxin control, and aseptic assurance. Residual bisphenol A monomers, oligomers, and trace processing aids in the recycled powder cannot be effectively removed. Long-term implantation poses risks of exudation leading to inflammation and rejection. These technologies fail to meet the biocompatibility standards of "Polyetheretherketone (PEEK) Resin for Surgical Implants" (YY / T 0660) and the GB / T 16886 series, and therefore cannot be directly used in the production of medical implants.
[0016] During SLS printing, the heating time and temperature environment of powder vary significantly in different areas of the forming cylinder: powder near the laser sintering zone is exposed to high temperatures for extended periods, resulting in deeper aging; powder on the surface and edges of the cavity is heated for shorter periods, resulting in less aging. Current technology, which mixes all waste powder for unified processing, inevitably leads to a contradiction: "slightly aged powder is overheated and undergoes secondary degradation, while moderately aged powder is insufficiently repaired." This results in batch-to-batch variations in molecular weight and melt flow rate of the recycled powder, which can reach 15%–20%, failing to meet the quality consistency requirements of medical device production. Typically, the powder can only be reused 1–2 times, making it economical and impractical for production.
[0017] Current recycling processes focus on physical sieving and morphology shaping, but do not address the chemical repair of molecular chain breakage caused by SLS high-temperature thermal aging, thus failing to reverse the trend of declining powder mechanical properties. After conventional physical recycling, the tensile strength of the powder decreases by 8% to 12% with each reuse, and after multiple reuses, the mechanical properties are far below implantable standards, posing a long-term clinical safety risk of fracture and deformation to the printed implants.
[0018] Personalized medical implants have stringent requirements for dimensional accuracy, surface roughness, and uniformity of pore structure. However, recycled powder has issues such as wide particle size distribution, decreased sphericity, and high ultrafine powder content, leading to uneven powder spreading, porosity defects in printed parts, and dimensional deviations. Existing recycling processes lack medical-grade precise particle size control and sphericity restoration steps, resulting in low printing yields of regenerated powder and failing to meet the production requirements of high-precision products such as craniofacial prostheses and spinal fusion devices.
[0019] This invention achieves safe, efficient, and medical-grade closed-loop regeneration of SLS medical PEEK waste powder through a fully closed-loop process including graded screening, solid-phase thickening, precise sieving, supercritical purification, and aseptic packaging, filling the technological gap in closed-loop recycling of medical-grade PEEK powder.
[0020] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows:
[0021] S1 Primary sorting and impurity removal pretreatment
[0022] After SLS 3D printing, unsintered waste PEEK powder is collected from the cavity. Various foreign objects are removed through a three-stage impurity removal process to obtain pretreated recycled powder. The specific operation is as follows:
[0023] S1-1 Primary Vibrating Screening: The collected waste powder is fed into a vibrating screener, using a 20-mesh (850μm) standard screen, with an amplitude of 1.5~2.0mm and a vibration frequency of 1400~1600 times / minute. Screening is carried out for 5~10 minutes to remove sintered lumps and large particles of foreign matter. The powder passing through the screen is collected for later use.
[0024] S1-2 Dual-stage Magnetoelectric Impurity Removal: The sieved powder is first subjected to a strong magnetic roller separator to remove ferromagnetic impurities, with a magnetic field strength ≥12000Gs; then it enters a high-voltage electrostatic impurity removal device, with an electric field strength of 80~120kV / m, to remove non-ferromagnetic metal particles and conductive impurities. The total content of metal impurities in the powder after treatment is ≤10ppm.
[0025] S1-3 Cyclone Dust and Fine Powder Removal: The powder after impurity removal is sent into the cyclone separator, and the inlet wind speed is controlled at 18~22m / s to remove light dust and fibrous debris with a particle size <5μm. The separation efficiency is ≥95%, which avoids the agglomeration and clumping of ultrafine powder during the printing process.
[0026] After pretreatment, the powder undergoes an initial visual inspection. If there are no visible foreign objects, the color is uniform, and there are no obvious yellow spots, it proceeds to the next stage of the process.
[0027] S2 Aging Level Grading Screening
[0028] The pretreated recycled powder adopts a two-stage grading mode of "rapid primary screening + precise secondary screening". Based on brand-new medical-grade PEEK powder, the powder is divided into three grades: mild aging, moderate aging, and severe aging according to the number average molecular weight retention rate, melt flow rate (MFR) change rate, and appearance color difference auxiliary indicators. Severely aged powder is directly rejected and downgraded for use, while mildly and moderately aged powders are collected separately and sealed for subsequent regeneration processes.
[0029] S2-1 Rapid Preliminary Screening: A near-infrared spectroscopy (NIR) online detection system is used for rapid batch identification. Based on a pre-established PEEK powder aging degree correction model, a single sample can be detected within 1 minute, with a processing efficiency of ≥50kg / h, and the aging level is initially classified.
[0030] S2-2 Precise Re-screening: For samples that fall within the grade boundary in the initial screening, high-temperature gel permeation chromatography (GPC) is used to determine the number-average molecular weight, and a melt flow rate (MFR) meter is used to determine the MFR, thus completing the precise grading. The GPC test conditions are: trichlorobenzene as solvent, test temperature 150℃, and narrow-distribution polystyrene as the standard; the MFR test conditions are: according to GB / T 3682.1 standard, 380℃, 2.16kg load, and preheating time 5min.
[0031] S2-3 Aging Level Classification Standard:
[0032] Mild aging: Number average molecular weight retention ≥90%, MFR change rate ≤15%, color difference ΔE ≤3.0, yellow index increase ≤2.0;
[0033] Moderate aging: Number average molecular weight retention rate is 75%~90%, MFR change rate is 15%~35%, color difference ΔE is 3.0~8.0, and yellow index increase is 2.0~6.0;
[0034] Severe aging: Number average molecular weight retention rate <75%, MFR change rate >35%, color difference ΔE >8.0, yellow index increment >6.0.
[0035] After grading, the powders are stored in sealed clean medical PE containers, labeled with grade and batch number, and mixed batches are strictly prohibited; heavily aged powders are collected and downgraded for use in industrial non-implantable fields, preventing them from entering the medical production process.
[0036] S3 Staged Vacuum Solid-Phase Viscosity Enhancement and Repair
[0037] The graded lightly and moderately aged powders are fed into a mirror-polished vacuum reactor with a jacket and heating system. They undergo low-temperature solid-phase thickening treatment under high-purity nitrogen protection and high vacuum environment. The molecular weight reduction caused by thermal aging is repaired through molecular chain end-group polycondensation reaction, so that the molecular weight and mechanical properties of the regenerated powder are restored to medical-grade standards. Different process parameters and heating programs are used for different aging levels to avoid secondary degradation and powder agglomeration.
[0038] S3-1 Pre-nitrogen purging: After the material is loaded and sealed, first evacuate to a vacuum degree ≤100Pa, then fill with high-purity nitrogen gas with a purity ≥99.999% to a slightly positive pressure. Repeat the purging 3 times to ensure that the oxygen content in the reactor is ≤50ppm, and prevent the powder from undergoing secondary thermal oxidation degradation during the thickening process.
[0039] S3-2 stepped heating program:
[0040] Dehydration stage: The temperature is increased to 180℃ at a rate of 5℃ / min and held for 2 hours to remove the trace amount of moisture adsorbed by the powder and avoid subsequent hydrolysis and degradation at high temperature.
[0041] Heating phase: Slowly increase the temperature to the target thickening temperature at a rate of 3℃ / min;
[0042] Thickening stage: Maintain constant temperature for the corresponding duration, and continuously stir at a low speed of 10~20 rpm during the process to ensure that the powder is heated evenly and the molecular weight distribution is narrower;
[0043] Cooling stage: After the reaction is completed, the temperature is gradually reduced to below 120°C at a rate of 2°C / min, and then nitrogen gas is introduced to rapidly cool it to room temperature to avoid slow cooling that could cause powder agglomeration.
[0044] S3-3 Differentiated Tackifying Process Parameters:
[0045] Slightly aged powder: processing temperature 220~240℃, vacuum degree ≤10Pa, processing time 4~8h; after repair, the number average molecular weight Mn≥32000, molecular weight distribution index PDI≤2.6, MFR controlled at 12~16g / 10min, and the deviation from brand new powder ≤10%;
[0046] Moderately aged powder: processing temperature 230~250℃, vacuum degree ≤5Pa, processing time 8~12h; after repair, the number average molecular weight Mn≥31000, molecular weight distribution index PDI≤2.8, MFR controlled at 13~17g / 10min, and the deviation from the new powder ≤15%.
[0047] S4 Multi-stage airflow sieving particle size control
[0048] The thickened and repaired PEEK powder is fed into a two-stage horizontal ceramic classifier airflow sieving system, with high-purity nitrogen gas (oxygen content ≤100ppm) purging throughout the process to precisely control the powder particle size distribution. For moderately aged powder, a low-temperature airflow shaping process is added before sieving to repair the powder sphericity, ultimately obtaining regenerated powder with uniform particle size and excellent flowability, meeting the high-precision powder spreading requirements of SLS.
[0049] S4-1 Optional Low-Temperature Airflow Shaping (essential for moderately aged powders): The viscous powder is fed into a low-temperature airflow mill. Under a low-temperature nitrogen atmosphere of 0~5℃, the powder is shaped by collisions caused by high-speed airflow, repairing irregular particles generated during the recycling process and improving the powder sphericity to ≥0.85. The process involves no media contact, avoiding the introduction of impurities.
[0050] S4-2 two-stage airflow classification process parameters:
[0051] First-stage coarse classification: Separates coarse particles with a diameter > 80 μm, with a classifying wheel speed of 1200~1500 rpm, a feed rate of 20~30 kg / h, and an airflow pressure of 0.6~0.8 MPa;
[0052] Second-stage sub-classification: Separates ultrafine dust with a particle size <20μm, with a classifying wheel speed of 3500~4000rpm and an airflow pressure of 0.5~0.7MPa.
[0053] S4-3 sieved powder performance indicators: particle size distribution range 20~80μm, median particle size D50=48~52μm, particle size span SPAN=(D90-D10) / D50≤1.8; loose density 0.48~0.52g / cm³, tapped density 0.68~0.72g / cm³, Hall flow rate ≤18s / 50g, powder spreading uniformity deviation ≤2%, with no significant difference in printing performance compared to brand new medical PEEK powder.
[0054] S5 Supercritical Fluid Impurity Removal
[0055] The sieved regenerated powder is fed into a medical-grade supercritical CO2 extraction vessel, where a "static soaking + dynamic circulation" composite extraction process is used in conjunction with a medical ethanol entrainer to deeply remove residual bisphenol A monomers, oligomers, and trace processing aids from the powder, ensuring that the impurity content meets the medical implant-grade standards; the CO2 can be recycled, and there is no waste liquid discharge.
[0056] S5-1 Pre-treatment: The inner wall of the extraction vessel is electrolytically polished to meet medical-grade hygiene requirements; the CO2 used is of food-grade purity or higher, and the entrainer is medical-grade anhydrous ethanol, which is used after being sterilized by 0.22μm filtration.
[0057] S5-2 composite extraction process flow:
[0058] After the material is loaded and sealed, the extraction vessel is first pressurized to the target pressure and heated to the target temperature, and then statically soaked for 1 hour to allow supercritical CO2 to fully penetrate into the powder particles.
[0059] The circulation system is started for dynamic extraction, the CO2 flow rate is controlled at 10~20kg / h, and the amount of entrainer added is 2%~5% of the total mass of CO2, which enhances the ability to dissolve and remove polar oligomers and residual monomers.
[0060] After extraction, the CO2 is separated by a two-stage separator under reduced pressure. The CO2 is then condensed, compressed, and recycled, with a recycling rate of ≥95%. The removed impurities are collected and treated regularly, with no waste liquid discharged.
[0061] S5-3 Optimal process parameters: extraction pressure 20MPa, extraction temperature 55℃, extraction time 3h, CO2 flow rate 15kg / h, entrainer addition 3%; under these parameters, the residual bisphenol A monomer removal rate is ≥90%, and the total oligomer removal rate is ≥85%.
[0062] After S5-4 removal, the impurity indicators are as follows: residual bisphenol A monomer ≤20ppm, total oligomer content ≤0.1%, and total heavy metal content ≤5ppm. All indicators are better than the requirements of YY / T 0660 standard.
[0063] S6 Medical-grade aseptic packaging and testing
[0064] The regenerated powder, after impurities are removed, undergoes deep vacuum drying, followed by aseptic packaging in a clean environment. Once it passes all type tests, it becomes the finished regenerated PEEK powder. The entire process complies with the GMP management standards for medical devices.
[0065] S6-1 Stepped Vacuum Drying: The powder is fed into a vacuum drying oven, first heated to 100℃ at 3℃ / min and held for 2 hours to remove surface adsorbed moisture; then heated to 130℃, with the vacuum degree controlled at ≤50Pa, and held for 8 hours to remove bound water inside the particles; after drying, the temperature is slowly lowered to below 40℃ before discharge to avoid the powder absorbing water and becoming damp again; the moisture content of the dried powder is ≤0.02%, avoiding water vaporization during SLS printing that could lead to pore defects and bubbles.
[0066] S6-2 Class 100 Cleanroom Aseptic Packaging: The packaging process is carried out under a Class 100 laminar flow hood in a Class 10,000 cleanroom, with operators dressed according to medical aseptic requirements. The packaging material is a medical-grade aluminum-plastic composite vacuum bag pre-sterilized by gamma rays. During packaging, a vacuum is first drawn to ≤10Pa, then high-purity nitrogen gas with a purity ≥99.999% is filled to a slightly positive pressure and then heat-sealed. The oxygen content inside the bag is ≤100ppm to prevent slow oxidation and aging of the powder during storage.
[0067] S6-3 Full Type Inspection and Release: Each batch of finished products must complete full type inspection, and can only be released after all indicators pass. The inspection items and applicable standards include:
[0068] Physicochemical properties: particle size distribution, molecular weight distribution, melt flow rate, moisture content, residual monomer content, heavy metal content;
[0069] Mechanical properties: tensile strength, flexural strength, and impact strength of simply supported beams (tested after 3D printing according to standard templates);
[0070] Biosafety: Cytotoxicity (GB / T 16886.5, MTT method), sensitization reaction (GB / T 16886.10), intradermal reaction (GB / T 16886.10), bacterial endotoxin (Chinese Pharmacopoeia gel method), sterility test (Chinese Pharmacopoeia).
[0071] Each batch of products comes with a quality inspection report and a unique traceability QR code, which records information such as raw material batch, process parameters, test results, and production personnel, meeting the traceability requirements for the entire life cycle of medical devices.
[0072] Additional notes: The regenerated powder prepared by this method can be used alone or mixed with virgin medical-grade PEEK powder in any proportion; the preferred mixing ratio is 30% to 70% regenerated powder. After mixing, the overall performance is not significantly different from that of virgin powder, which can further improve production flexibility and reduce production costs.
[0073] Compared with the prior art, the present invention has the following significant technical advancements and beneficial effects:
[0074] 1. The entire process is under medical-grade control, and the biosafety fully meets the requirements for Class III implants.
[0075] This invention establishes a comprehensive quality control system for medical implant applications, encompassing impurity removal and aseptic packaging. It utilizes supercritical CO2 entrainer extraction technology to deeply remove residual monomers and oligomers, coupled with Class 100 cleanroom aseptic packaging. The finished powder exhibits residual bisphenol A monomer ≤20ppm, endotoxin ≤0.5EU / g, and cytotoxicity ≤Grade 1, with no sensitization or intradermal irritation. The sterility level meets the requirements of the Chinese Pharmacopoeia, and all indicators surpass the YY / T 0660 industry standard. This completely solves the problem of substandard biosafety in existing industrial recycling processes. The recycled powder can be directly used in the production of Class III orthopedic and craniofacial implants.
[0076] 2. The graded and differentiated regeneration mode significantly improves batch stability and performance consistency.
[0077] This invention pioneers a graded regeneration process based on "aging classification and parameter matching." Through a two-stage classification system of near-infrared rapid primary screening followed by GPC precise secondary screening, powders with different degrees of thermal aging are classified and processed, and corresponding solid-phase thickening process parameters are matched. This avoids the technical drawbacks of traditional uniform processing, such as "excessive degradation of mildly aged powders and insufficient repair of moderately aged powders." The batch-to-batch deviation of the regenerated powder is ≤3% in number-average molecular weight, ≤5% in MFR, and ≤3% in mechanical properties, far exceeding the 15%~20% deviation level of existing recycling processes. This fully meets the batch consistency requirements for medical device production and provides technical support for large-scale stable production.
[0078] 3. Solid-phase thickening reverses molecular chain breakage, significantly increasing the number of reuses and raw material utilization.
[0079] By employing low-temperature vacuum solid-state polycondensation technology, the broken molecular chain end groups are re-polymerized without damaging the powder morphology, effectively reversing the molecular weight decay and mechanical property degradation caused by high-temperature aging of SLS. Compared with existing recycling technologies that only involve physical sieving, the mechanical property retention rate of the regenerated powder in this invention is increased from 75%~85% to over 94%, and the number of powder recycling cycles is increased from 1~2 times to ≥5 times. Combined with a graded screening mechanism, the powder raw material utilization rate of the SLS process is increased from the traditional 25%~35% to over 80%, and the printing output per kilogram of powder is increased by more than 2 times. This can reduce the raw material cost of medical PEEK implants by more than 60%, resulting in significant economic benefits.
[0080] 4. Precise particle size control and sphericity correction, suitable for high-precision medical SLS printing.
[0081] Narrow particle size distribution is controlled through multi-stage airflow sieving, and the sphericity of the powder is restored by low-temperature airflow shaping technology, so that the flowability and powder spreading uniformity of the regenerated powder are comparable to those of virgin powder. PEEK implants printed with the regenerated powder of this invention have a dimensional accuracy deviation of ≤±0.05mm, a surface roughness Ra≤6.3μm, a pore structure deviation of ≤2%, and an interlayer bonding strength ≥92% of that of parts printed with virgin powder. There are no obvious interlayer cracks or pore defects, which fully meet the printing quality requirements of high-precision personalized implants such as craniofacial prostheses, spinal fusion devices, and dental implants. The printing yield is ≥98%, which is not significantly different from the yield of parts printed with virgin powder.
[0082] 5. Green and clean technology, easy for industrial-scale mass production.
[0083] This invention employs a predominantly physical process, eliminating the use of toxic or harmful chemical reagents, heavy metal additives, and wastewater and waste residue emissions. Supercritical CO2 is recyclable with a recycling rate of ≥95%, resulting in low energy consumption and environmental friendliness. Each process unit utilizes mature industrial equipment, requiring no customized special equipment. Process parameters are highly controllable, with a single batch processing capacity of 50-200 kg, facilitating industrial-scale mass production. Furthermore, the entire process is fully automated, complying with GMP production management standards for medical devices, and possesses significant value for industrial application and promotion.
[0084] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. Attached Figure Description
[0085] Figure 1 This is a flowchart of the overall process.
[0086] Figure 2 Schematic diagram of the aging classification screening principle;
[0087] Figure 3 Schematic diagram of a vacuum solid-phase viscosity-enhancing repair device;
[0088] Figure 4 This is a flowchart of particle size control and supercritical extraction.
[0089] Figure 5 This is a schematic diagram of closed-loop regeneration. Detailed Implementation
[0090] The technical solution of the present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments. All technologies and processes implemented based on the content of the present invention fall within the scope of the present invention. Without departing from the spirit and scope of the present invention, those skilled in the art can make appropriate adjustments or equivalent substitutions to the process parameters, and all such adjustments should be covered within the scope of protection of the present invention.
[0091] The raw material standards used in the various embodiments and comparative examples of the present invention are as follows:
[0092] New medical implant-grade PEEK powder: conforms to YY / T 0660-2021 standard "Polyetheretherketone (PEEK) Resin for Surgical Implants", number average molecular weight Mn=34800, melt flow rate MFR=14.2g / 10min (test conditions: 380℃, 2.16kg load, preheating for 5min), particle size distribution 20~80μm, median particle size D50=49.6μm, residual bisphenol A monomer content 12ppm, bacterial endotoxin < 0.03EU / g, cytotoxicity grade 0.
[0093] Waste PEEK powder is recycled from unsintered waste powder obtained after printing personalized craniofacial prostheses using an industrial-grade medical SLS 3D printer (forming cylinder size 250mm×250mm×300mm). Printing process parameters: preheating temperature 360℃, laser power 15W, scanning speed 2000mm / s, layer thickness 0.1mm, single continuous printing time 48h. After printing, the cavity is naturally cooled to room temperature, and all unsintered powder is aseptically collected as recycled raw material.
[0094] Example 1: Graded regeneration treatment of slightly aged PEEK powder
[0095] This embodiment focuses on the regeneration of slightly aged SLS-recycled PEEK powder. The specific steps are as follows:
[0096] S1 Primary sorting and impurity removal pretreatment
[0097] Take 10 kg of the above-mentioned recycled waste powder and feed it into a vibrating screen. Use a 20-mesh (850 μm) standard screen, set the amplitude to 1.8 mm and the vibration frequency to 1500 times / minute, and screen for 8 minutes to remove sintered lumps and large particles of foreign matter, and collect the powder that passes through the screen.
[0098] The sieved powder is passed through a high-intensity magnetic roller separator (magnetic field strength 12000Gs) to remove ferromagnetic impurities, and then enters a high-voltage electrostatic purification device (electric field strength 100kV / m) to remove non-ferromagnetic metal particles.
[0099] Finally, the purified powder is fed into a cyclone separator, with the inlet air velocity controlled at 20 m / s, to remove light dust and fiber debris with a particle size of <5 μm.
[0100] Tests showed that the total content of metal impurities in the pretreated powder was 7.2 ppm, with no visible foreign matter and a uniform color without obvious yellow spots.
[0101] S2 Aging Level Grading Screening
[0102] For pretreated powder samples, a rapid initial screening was first performed using a near-infrared spectroscopy (NIR) online detection system, followed by precise secondary screening using high-temperature gel permeation chromatography (GPC) and a melt flow rate analyzer.
[0103] The number-average molecular weight Mn = 32430, with a retention rate of 93.2% based on virgin powder.
[0104] The melt flow rate (MFR) was 15.8 g / 10 min, with a change rate of 11.3%.
[0105] The color difference ΔE = 2.1, and the yellow index increment is 1.5.
[0106] If the powder meets the criteria for mild aging, it will be collected separately in a sealed container and then proceed to the subsequent regeneration process.
[0107] S3 Staged Vacuum Solid-Phase Viscosity Enhancement and Repair
[0108] The slightly aged powder was fed into a mirror-polished vacuum solid-phase reactor with a jacketed heating system. After loading and sealing, nitrogen purging was performed: first, the vacuum was evacuated to a vacuum degree of 80 Pa, and then high-purity nitrogen with a purity of 99.999% was introduced to a slightly positive pressure. The purging was repeated 3 times, and the final oxygen content in the reactor was 32 ppm.
[0109] A stepped temperature increase process is used for viscosity enhancement.
[0110] Dehydration stage: The temperature is increased to 180℃ at a rate of 5℃ / min and kept at that temperature for 2 hours to remove the trace amount of moisture adsorbed by the powder.
[0111] Heating phase: Slowly increase the temperature to 230℃ at a rate of 3℃ / min;
[0112] Thickening stage: Control the vacuum degree to 8Pa, stir continuously at a low speed of 15rpm, and maintain the constant temperature for 6h;
[0113] Cooling stage: After the reaction is completed, the temperature is gradually reduced to 110°C at a rate of 2°C / min, and then high-purity nitrogen is introduced to rapidly cool it to room temperature before discharging.
[0114] S4 Multi-stage airflow sieving particle size control
[0115] The thickened and repaired powder is fed into a two-stage horizontal ceramic classifying and sieving system, with high-purity nitrogen gas (oxygen content ≤80ppm) purging throughout the process.
[0116] First-stage coarse classification: Classifying wheel speed 1350rpm, feed rate 25kg / h, air pressure 0.7MPa, separating and removing coarse particles with a particle size >80μm;
[0117] Second-stage sub-classification: the classifying wheel rotates at 3800 rpm and the airflow pressure is 0.6 MPa, separating and removing ultrafine dust with a particle size of <20 μm.
[0118] After sieving, the powder particle size properties were tested: median particle size D50 = 50.2 μm, particle size span SPAN = 1.62, loose density 0.50 g / cm³, tapped density 0.70 g / cm³, Hall flow rate 16.8 s / 50 g, and powder spreading uniformity deviation 1.2%.
[0119] S5 Supercritical Fluid Impurity Removal
[0120] The sieved powder is fed into a medical-grade supercritical CO2 extraction vessel, employing a combined extraction process of "static soaking + dynamic circulation":
[0121] After the material is loaded and sealed, the extraction vessel is pressurized to 20 MPa and heated to 55°C, and statically soaked for 1 hour to allow supercritical CO2 to fully penetrate into the powder particles.
[0122] The circulation system was turned on for dynamic extraction for 2 hours, the CO2 flow rate was controlled at 15 kg / h, and medical anhydrous ethanol accounting for 3% of the total CO2 mass was added as an entrainer to enhance the removal effect of polar impurities.
[0123] After extraction, the CO2 is separated by a two-stage separator under reduced pressure. The CO2 is then condensed, compressed, and recycled, with a recycling rate of 96.2%.
[0124] S6 Medical-grade aseptic packaging and testing
[0125] Stepped vacuum drying: The extracted powder is sent into a vacuum drying oven. First, the temperature is increased to 100℃ at 3℃ / min and kept at this temperature for 2 hours to remove surface adsorbed water. Then, the temperature is increased to 130℃, the vacuum degree is controlled at 45Pa, and the temperature is kept at this temperature for 8 hours to remove the bound water inside the particles. After drying, the temperature is slowly reduced to below 35℃ and the powder is discharged. The moisture content of the powder is 0.012%.
[0126] Aseptic packaging: The packaging process is carried out under a Class 100 laminar flow hood in a Class 10,000 cleanroom, using medical-grade aluminum-plastic composite vacuum bags that have been pre-sterilized by gamma rays; during packaging, the vacuum is first drawn to 8Pa, then filled with 99.999% high-purity nitrogen to a slightly positive pressure and then heat-sealed, with the oxygen content inside the bag being 78ppm.
[0127] Full-item testing and release: The finished powder was subjected to full-item performance testing, and the results of key indicators are shown in Table 1.
[0128] Example 2: Graded Regeneration Treatment of Moderately Aged PEEK Powder
[0129] This embodiment focuses on the regeneration of moderately aged SLS-recycled PEEK powder. The overall process flow is the same as in Example 1, with key parameters adjusted according to the aging level, as follows:
[0130] S1 Primary sorting and impurity removal pretreatment
[0131] Following the same steps as in Example 1, the total content of metal impurities in the powder after treatment was 6.8 ppm.
[0132] S2 Aging Level Grading Screening
[0133] Testing revealed that the number-average molecular weight (Mn) of the recovered powder in this batch was 28710, with a retention rate of 82.5%; the molecular weight ratio (MFR) was 18.1 g / 10 min, with a change rate of 27.4%; the color difference (ΔE) was 5.7, and the yellow index increment was 4.2, meeting the criteria for moderate aging. The powder was collected in an independently sealed container.
[0134] S3 Staged Vacuum Solid-Phase Viscosity Enhancement and Repair
[0135] After nitrogen purging, the oxygen content in the reactor was 28 ppm. The step heating program was the same as in Example 1, and the core thickening parameters were adjusted as follows: processing temperature 240℃, vacuum degree 4Pa, constant temperature thickening time 10h, and stirring speed 12rpm.
[0136] S4 Multi-stage airflow sieving particle size control
[0137] Before sieving, a low-temperature airflow shaping process is added: the thickened powder is fed into a low-temperature airflow mill, and under a low-temperature nitrogen atmosphere at 3°C, the powder is shaped by high-speed airflow through collisions, repairing irregular particles. The sphericity of the shaped powder is 0.87.
[0138] After shaping, the material was subjected to two-stage airflow sieving, with the same process parameters as in Example 1. Post-sieving measurements: D50 = 49.1 μm, SPAN = 1.71, loose packing density 0.49 g / cm³, Hall effect velocity 17.5 s / 50 g.
[0139] S5 Supercritical Fluid Impurity Removal
[0140] The extraction process parameters were adjusted to: extraction pressure 22MPa, extraction temperature 58℃, total extraction time 3.5h, CO2 flow rate 18kg / h, and entrainer addition amount 4%, to enhance the deep removal effect.
[0141] S6 Medical-grade aseptic packaging and testing
[0142] The drying and packaging process is the same as in Example 1.
[0143] Example 3: Performance Verification of Multiple Cycle Reuse
[0144] This embodiment verifies the performance stability of the powder after multiple cycles of regeneration:
[0145] The regenerated powder prepared in Example 1 was used to print standard mechanical splines and simulated implants according to the same SLS process parameters as the original printing. After printing, the unsintered waste powder was collected and regenerated again using the full process of Example 1. The above "print-recycle-regenerate" cycle was repeated for 5 consecutive cycles. The core performance of the regenerated powder was tested after the 1st, 3rd and 5th cycles, and the results are shown in Table 2.
[0146] Comparative Example 1: Traditional Simple Screening and Recycling Process
[0147] The recycled powder from the same batch as in Example 1 was subjected to a simple recycling process that is common in the industry: large lumps were removed by 20-mesh vibrating sieve, and the particle size was adjusted by 80μm airflow sieve. There was no aging grading, no solid phase thickening repair, no supercritical impurity removal, and no medical-grade aseptic packaging.
[0148] Comparative Example 2: Ungraded Uniform Tackification Process
[0149] Equal amounts of lightly aged and moderately aged recycled powders were uniformly mixed without aging grading. The lightly aged thickening parameters of Example 1 were used for processing. The remaining screening, extraction, and packaging processes were the same as in Example 1.
[0150] Effect Analysis
[0151] 1. Medical safety meets standards: The residual monomers, endotoxins, cytotoxicity and other biosafety indicators of the recycled powders in Examples 1 and 2 all meet the requirements of YY / T 0660 and GB / T 16886 standards and can be directly used for the production of Class III implants; while the endotoxins and cytotoxicity of the simple screening process in Comparative Example 1 exceed the standards and cannot meet the requirements for medical implantation.
[0152] 2. Graded processing improves consistency: The molecular weight and mechanical properties of Examples 1 and 2 have small deviations and excellent batch stability; Comparative Example 2, without graded and unified processing, resulted in insufficient repair of moderately aged powder, large overall performance deviation, and could not meet the consistency requirements of medical device production.
[0153] 3. Significant mechanical property restoration: Through solid-phase thickening process, the mechanical property retention rate of the powder in the example reached over 94%, which is much higher than the approximately 82% of Comparative Example 1. This effectively reversed the performance degradation caused by thermal aging and reduced the risk of long-term implant breakage.
[0154] 4. Excellent recycling capacity: After five consecutive cycles, the powder performance still meets medical-grade standards, and the raw material utilization rate has increased from less than 30% in the traditional way to more than 80%, which greatly reduces the production cost of medical PEEK implants.
[0155] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.
Claims
1. A graded regeneration method for SLS 3D printing PEEK recycled powder, characterized in that, The steps are as follows: (1) Primary sorting and impurity removal pretreatment: Collect unsintered waste PEEK powder after SLS 3D printing, and remove sintered agglomerates, metal impurities and ultrafine dust through a three-stage impurity removal process of vibration sieving, magnetic and electric impurity removal and cyclone dust removal to obtain pretreated recycled powder; (2) Aging degree classification and screening: Based on the new medical grade PEEK powder, according to the number average molecular weight retention rate and the melt flow rate change rate, the pretreated powder is divided into three grades: mild aging, moderate aging and severe aging. Severely aged powder is removed, and mildly aged and moderately aged powder are collected separately in sealed containers. (3) Graded vacuum solid phase thickening repair: The graded lightly aged and moderately aged powders are placed in a vacuum reactor and subjected to low-temperature solid phase thickening treatment under high-purity nitrogen protection and high vacuum environment. Different treatment temperatures, vacuum degrees and heat preservation times are matched for different aging levels. The molecular chain breakage caused by thermal aging is repaired by molecular chain end-group polycondensation reaction, and the mechanical properties of the powder are restored. (4) Multi-stage airflow sieving particle size control: The viscous and repaired PEEK powder is fed into a two-stage airflow classification system to precisely control the particle size distribution range and median particle size of the powder, so as to obtain regenerated powder with uniform particle size and flowability that meets the requirements of SLS high-precision powder spreading. (5) Supercritical fluid impurity removal: The extraction process using supercritical CO2 combined with medical entrainer is used to deeply remove residual bisphenol A monomers, oligomers and trace processing aids from the powder, so that the impurity content meets the medical implant grade standard. (6) Medical-grade aseptic packaging and testing: The powder after impurity removal is subjected to step vacuum drying, and then aseptic packaging is completed in a clean environment. After passing all performance tests, the finished medical-grade regenerated PEEK powder is obtained.
2. The graded regeneration method for SLS 3D printing PEEK recycled powder according to claim 1, characterized in that, The aging level classification criteria mentioned in step (2) are as follows: Mild aging: Number average molecular weight retention ≥90%, melt flow rate change ≤15%; Moderate aging: Number average molecular weight retention rate is 75%~90%, and melt flow rate change rate is 15%~35%; Severe aging: Number average molecular weight retention rate <75%, melt flow rate change rate >35%.
3. The graded regeneration method for SLS 3D printing PEEK recycled powder according to claim 2, characterized in that, The process parameters for differentiated solid-phase thickening in step (3) are as follows: Slightly aged powder: processing temperature 220~240℃, vacuum degree ≤10Pa, constant temperature processing time 4~8h; Moderately aged powder: processing temperature 230~250℃, vacuum degree ≤5Pa, constant temperature processing time 8~12h; Throughout the thickening process, the oxygen content inside the reactor is controlled below 50 ppm. A stepped heating and low-speed stirring mode is used to avoid secondary thermal oxidation degradation and agglomeration of the powder.
4. The graded regeneration method for SLS 3D printing PEEK recycled powder according to claim 1, characterized in that, The specific process of the two-stage airflow classification in step (4) is as follows: the first stage coarse classification separates coarse particles with a particle size > 80 μm, and the classification wheel speed is 1200~1500 rpm; the second stage fine classification separates ultrafine dust with a particle size < 20 μm, and the classification wheel speed is 3500~4000 rpm; the particle size distribution range of the powder after sieving is 20~80 μm, the median particle size D50 is 48~52 μm, and the particle size span SPAN≤1.
8.
5. The graded regeneration method for SLS 3D printing PEEK recycled powder according to claim 1, characterized in that, The supercritical CO2 extraction in step (5) adopts a composite process of "static soaking + dynamic circulation". The specific parameters are: extraction pressure 15~25MPa, extraction temperature 45~60℃, total extraction time 2~4h, CO2 flow rate 10~20kg / h; the entrainer is medical anhydrous ethanol, and the amount added is 2%~5% of the total mass of CO2.
6. The graded regeneration method for SLS 3D printing PEEK recycled powder according to claim 1, characterized in that, The step-by-step vacuum drying process described in step (6) is as follows: first, the temperature is raised to 100℃ at 3℃ / min and kept at that temperature for 2 hours to remove surface adsorbed water; then, the temperature is raised to 120~140℃, the vacuum degree is controlled to be ≤50Pa, and the temperature is kept at that temperature for 6~10 hours to remove the bound water inside the particles. After drying, the moisture content of the powder is ≤0.02%. The aseptic packaging is carried out in a Class 100 clean environment, using a pre-sterilized medical-grade aluminum-plastic composite vacuum bag. After vacuuming, it is filled with high-purity nitrogen and sealed. The oxygen content inside the bag is ≤100ppm.
7. The graded regeneration method for SLS 3D printing PEEK recycled powder according to claim 1, characterized in that, The specific parameters of the three-stage impurity removal process described in step (1) are as follows: Vibrating screen: Uses a 20-mesh standard screen, amplitude 1.5~2.0mm, vibration frequency 1400~1600 times / minute to screen out large sintered lumps; Magnetoelectric impurity removal: First, ferromagnetic impurities are removed by strong magnetic roller separation with a magnetic field strength ≥12000Gs, and then non-ferromagnetic metal particles are removed by high voltage electrostatic field of 80~120kV / m. The total content of metal impurities in the powder after treatment is ≤10ppm. Cyclone dust removal: Control the inlet air velocity to 18~22m / s to remove light dust and fiber debris with a particle size <5μm.
8. A graded regeneration method for SLS 3D printing PEEK recycled powder according to claim 1, characterized in that, In step (4), before the moderately aged powder is subjected to airflow sieving, a low-temperature airflow shaping process is added: under a low-temperature nitrogen atmosphere of 0~5℃, the powder is driven to collide with each other by high-speed airflow to repair the sphericity of the powder to ≥0.
85.
9. A graded regeneration method for SLS 3D printing PEEK recycled powder according to claim 1, characterized in that, The resulting recycled powder can be used alone or mixed with brand-new medical-grade PEEK powder in any proportion, both of which can meet the SLS printing production requirements for Class III medical PEEK implants.